Genetic structure of pest polydorids (Annelida: Spionidae) infesting Crassostrea gigas in southern Africa : are pests being moved with oysters? - Williams, Lee-Gavin (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc) -- Stellenbosch University, 2015.